Peningkatan Mutu dan Kemampuan Pelayanan Laboratoriumoratorium di RS Harapan Sehati - Suprayogi, Eko (UI Scholars Hub, 2020)
According to Permenkes RI No. 411/Menkes/Per/III/2010, Clinical Laboratoriumoratory is a health laboratoriumoratory that carries out clinical specimen examination services to obtaininformation about individual health, especially to support efforts to diagnose diseases, and restore health. Therefore, clinical laboratoriumoratory requirements have also been determined according to its level (pratama, middle or major). The Harapan Sehat Hospital (Harti Hospital) is a hospital that was physically built as a General Hospital with a classification of C with a capacity of 110 beds (TT). The profile of the laboratoriumoratory at Harti Hospital, prior to repairs, was the pratama general clinical laboratoriumoratory that collaboratoriumorated with outside laboratoriumoratories for several types of examinations. From the results ofthe processed data, interviews and observations, then conducted the first brainstorming to identify problems using the 'fish bone' method Isikawa, it was concluded that there were several problems including high response time (> 2 hours) and many examination cases that had to be referred out of hospital because of the type / item inspection tools are limited and the lack of analysts and IT support is still limited. The priority of the problem is determined through the USG (Urgency, Seriousness, Growth) method. Referring to the findings of the problem, the management made a program which included adding technical analysts and rejuvenation programs and increasing the ability of laboratoriumoratory equipment. As a result, the number of referred examination cases dropped dramatically from the initial 20% referred (staying for special examinations) to 0% and Response Time decreased considerably from more than 2 hours to 40 minutes for cito examinations. Considering that in the future there will be more and more diverse samples examined, it is recommended to increase IT support, the work system (work management) in the laboratorium must be continuously improved, equip tools for inspection items (especially special examinations) and add analysts as needed.